Effects of speed feedback trailer positioning and police enforcement on vehicular speeds in freeway work zone lane closures - Shakir Mahmud, Md; Jashami, Hisham; Usamah Megat Johari, Megat; Gupta, Nischal; Bamney, Anshu; Gates, Timothy J.; Savolainen, Peter (SAGE Publications, 2024)
This field study sought to evaluate select strategies for improving compliance with work zone speed limits, which included a speed feedback trailer (SFT) and active police enforcement. The initial evaluation included an SFT positioned at the start or end of the taper within a freeway single-lane closure to determine which position provided the most favorable speed reductions. Positioning the SFT near the end of the taper caused the speed reductions to be sustained over a greater distance into the work zone compared with when the SFT was positioned near the start of the taper. With the SFT positioned near end of the taper, the average speed was 1.5 mph lower at the end of the taper and 0.8 mph lower 1,350-ft beyond the end of the taper compared with when the SFT was inactive. The second evaluation assessed the effectiveness of a specialized work zone enforcement strategy that included a covert speed measurement vehicle positioned near the end of the work zone along with four police cars positioned just beyond the end of the work zone to stop speeding drivers. This speed enforcement strategy reduced work zone speeds by up to 7 mph, on average, shortly beyond the end of the work zone as motorists passed by the police cars positioned on the shoulder. These speed reductions were only observed when at least one law enforcement vehicle was visibly present at the site.